Galois Field Hardware Architectures for Network Coding - Nagarayan, Aishwarya (My University, 2010)
This paper presents and analyzes novel hardware designs for high-speed network coding. Our designs provide efficient methods to perform Galois field (GF) dot products and matrix inversions, which are important operations in network coding. Encoder designs that that perform GF dot products and vary with respect to the number of messages combined, Galois field size, and input message size are implemented and analyzed to evaluate design tradeoffs. We investigate single cycle, multi-cycle, and pipelined designs with and without feedback mechanisms for encoding multiple sets of messages. The decoder is implemented as a multi-cycle design and performs GF matrix inversion followed by multiple GF dot products. Our designs are synthesized with a 65nm standard cell library and compared in terms of area, clock period and throughput. Designs combining four messages achieve throughputs of more than 30 Gbps. Our designs can scale to achieve much higher throughput through the use of additional hardware.
Keywords: Router Designs; Gauss-Jordan elimination; Matrix inversion; Galois field arithmetic; Networks; Content Distribution; Network coding